Offshoring And Financial Markets - Gianfranco Battisti (European Regional Science Association (ERSA), 2013)
During the 20th century all economic structures underwent the impact of two epochal phenomena, the communications revolution and the financialization of economy. As a consequence of the never ending technological progress, the first has repeatedly reduced the friction of distance, provoking a radical change in the map of locational advantages. The result was a new model of international distribution of production that projected its effects to the core of business management, triggering a disintegration of production cycles in contrast with the integrative pattern typical of the first industrial revolution. The second phenomenon, strictly linked to the first one, apparently regards only the tertiary sector, but in reality it is becoming the driving force that influences, directly or in indirectly, a growing share of corporates. It follows that the reassuring models of spatial economy theorized during the 19th and 20th centuries (Thünen, Weber, Christaller), despite their updatings (Berry, Hoover, Alonso etc.) are no longer suitable to understand the present-day economic landscape. At the same time it appears of primary importance to define a model of financial space, shaped by the intertwining of capital movements, as a sort of virtual reality largely superordinate to the real economic world, this latter receiving from it the impulses which command the geographical distribution of productions. Obviously in the frame of a globalized economy the geographical range to be considered is the whole of our planet. Following the postulates at the basis of an isotropic space, where we must arrange both homogeneous and heterogeneous phenomena, various approaches are available. In fact we may begin studying a) the areas considered homogeneous according to some parameters concerning the capitals market, b) the ?strong points? (representing concentrations of financial capital), c) the ?discontinuity faults?, d) the capital flows itself. In the present work, which is part of a wider effort to formalize the subject, we focus on a peculiar type of discontinuity surfaces, the so-called ?tax havens?. In the economics domain, tax havens are the tantamount of black holes in astrophysics. These latter swallow matter and eject energy and water. What the two concepts have in common is a deep transformation of the input and the capacity to modify the surrounding environment, changing its architecture and the way it works. With the emergence of the financial crisis in 2008 the subject of tax havens has attracted growing attention from the governments of the leading Western economies. This stimulates the economic geographer to fill the academic gap and make the subject more readable. On the basis of real cases that recently gained wide publicity we outline the role of such institutions in the financial space.
Keywords: F36; F65; G15; N2; O16; 330; financial space; offshoring; tax haven